Influence of ethylene and ethephon treatments on the peel color and carotenoids of Gannan Newhall navel orange during postharvest storage. Issue 5 (12th March 2018) - Hu, Yuying; Wang, Guanghong; Pan, Siyi; Wang, Lufeng
Abstract: Gannan Newhall navel orange was treated by ethylene and ethephon separately. The color of Gannan Newhall navel orange peel was influenced significantly by ethylene and ethephon treatments. During postharvest storage, the ratio of chlorophylls and carotenoids in the peel reduced which led the peel color changing from green to yellow when treated by ethephon and to orange‐red when treated by ethylene. Results of the CIELAB chroma system evaluation were consistent with sensory evaluation. Ethylene and ethephon treatments decreased β‐carotene and lutein contents and increased β‐cryptoxanthin content largely (converted β‐carotene to β‐cryptoxanthin) in citrus peel. Besides, ethylene and ethephon treatments could convert yellow violaxanthin to neoxanthin or zeaxanthin. In ethylene treatment, its peel color changing to orange‐red due to β‐cryptoxanthin converted to β‐citraurin, which made Gannan Newhall navel orange exhibited the welcomed color (orange‐red). It was desirable for citrus postharvest process. Practical applications: The color of citrus fruit has become an important factor affecting fresh fruit price and market competitiveness. Studies have shown that citrus peel color is mainly affected by the content and proportion of chlorophylls and carotenoids. This study is aimed to illustrate the transformation of carotenoids and the mechanism of regulation of ethylene on the navel orange peel changing from green to orange‐red. The results of this research could provide scientific supports for citrus's atmosphere controlled storage, which could produce added value.